Fixed Assets Revaluation and Future Firm Performance: Empirical Evidence from Indonesia - Achmad Faizal Azmi; Syaiful Ali (The Indonesian Journal of Accounting Research, 2019)
Indonesia's government issued a temporary tax cut law in 2015, which serves as a tax incentive that encourages Indonesian firms to revalue their fixed assets and disclose them in the financial statements according to the assets' fair value. We investigate the association between the revaluation of fixed assets and future firm performance for Indonesian firms. The result shows that the revaluation of fixed assets by Indonesian firms is significantly positively associated with changes in operating income one year after revaluation. Meanwhile, there is no positive association between the revaluation of fixed assets and operating cash flow after two years of revaluation. This result implied that the motivation of revaluation is mainly related to the effort to disclose the fair value of the fixed assets to the user of financial statements. We can conclude that the temporary tax cut law is effective in fostering the future operating performance of the Indonesian firms.